“PATRIMONIALIZAÇÃO DO PATRIMÔNIO”: ENSAIO SOBRE A RELAÇÃO ENTRE TURISMO, “PATRIMÔNIO CULTURAL” E PRODUÇÃO DO ESPAÇO - Cruz, Rita de Cássia Ariza da (GEOUSP Espaço e Tempo (Online), 2012)
This text aims to build a critical analysis of the relationship between tourism, heritage and production of space. For this purpose, we start discussing the concept of culture and cultural heritage and, from there, we argue about what we called here "patrimonialization of heritage", namely the institutionalization of mechanisms for protection of cultural material and immaterial heritage. This reflection is guided by a fundamental premise: the recognition that these processes are part of the conflicting and contradictory space production, housing, therefore, within it a multitude of contradictions. These contradictions are discussed one by one, throughout the our argumentation.